Two new species of Bradynobaenus Spinola, 1851 (Hymenoptera: Bradynobaenidae) in the semiarid area of Argentina - Torréns, Javier; Fidalgo, Patricio (Zootaxa, 2017)
Bradynobaenus diminutus Torréns & Fidalgo, sp. nov. and B. porteri Torréns & Fidalgo, sp. nov. (Argentina: La Rioja) are described and illustrated. A revised key of the genus is provided.